(Finding) Pathways out of homelessness: An engaged, trans-disciplinary collaborative in the City of Tshwane. Issue 4 (4th July 2017) - de Beer, Stephan; Vally, Rehana
ABSTRACT: Street homelessness in the City of Tshwane was brought to public attention in the winter of 2014. This led to a composite research project involving different constituencies, including homeless people, to reflect on ways of addressing street homelessness in the city. This article serves as a conceptual and epistemological introduction to this collaborative research project entitled Pathways Out of Homelessness. The article argues for the use of a broad working definition of street homelessness that allows for complexities of homelessness to emerge, in order to discern diverse and appropriate alternatives.